THU0314 Rheumatoid Arthritis Patients with Fibromyalgic Clinical Features Have Significantly Less Synovitis as Defined by Power Doppler Ultrasound. (9th June 2015) - Mian, A.; Chaabo, K.; Wajed, J.; Kirkham, B.; Garrood, T.
Abstract : Background: An estimated 20% of patients with rheumatoid arthritis (RA) have coexisting fibromyalgia (FM). The presence of FM can make treatment decisions challenging, as disease activity scores can be high despite limited clinical evidence of active synovitis. Ultrasound is being increasingly used in clinical practice to detect subclinical synovitis. Recent work by Pollard et al 1 has suggested that a tender joint count (out of 28) (TJC) minus swollen joint count (SJC) of at least 7 ("joint count criteria") predicts RA patients who meet the 1990 ACR FM classification criteria 2 ("tender point criteria"). Objectives: To determine whether RA patients meeting criteria for fibromyalgia have significantly less ultrasonographic joint inflammation. Methods: 47 RA patients with DAS28 scores >2.6 were recruited. Patients completed PHQ9 (depression), PHQ15 (somatisation), FACIT-fatigue, HAQ, global health and visual analogue score (VAS) questionnaires. The SJC, TJC and the number of fibromyalgia soft-tissue tender point, as defined by the 1990 ACR classification criteria were recorded. Patients underwent a blinded 22 joint ultrasound scan (wrists, MCPJs and PIPJs bilaterally). Grey scale (GSUS) and power Doppler (PDUS) scores were recorded for each joint (scale 0-3) and each summed to give a total score. Patients were grouped according to the above mentioned criteria individually and in combination. Differences between groups were tested using the Mann-Whitney U test. Significance was set at p<0.05. Results: DAS28 scores were significantly higher in patients meeting either the tender point or joint count criteria. Patients meeting either criteria scored significantly higher for PHQ9, PHQ15, FACIT-fatigue and HAQ. Despite the higher DAS scores, GSUS scores were significantly lower in patients meeting the joint count criteria (17.1 vs 22.5, p=0.034), tender point criteria (16.6 vs 21.7, p=0.025), or both criteria (15.4 vs 21.8, p=0.022). PDUS scores for patients meeting either criteria were lower but the differences were not significant. Patients meeting both criteria had significantly lower scores (2.94 vs 8.33, p=0.28). Conclusions: Our findings show that RA patients who fit the 1990 ACR classification criteria for fibromyalgia and who have a tender joint minus swollen joints count of ≥7 have significantly lower levels of synovitis on ultrasound with lower grey scale and power Doppler scores. This suggests that may be a role for composite tools in clinical practice to help stratify patients into those that may benefit from escalation of disease-modifying therapy and those that may benefit from alternative management strategies. Further work to identify stratification tools using clinical criteria is ongoing. References: Pollard LC, Kingsley GH, Choy EH, Scott DL. Fibromyalgic rheumatoid arthritis and disease assessment. Rheumatology 2010;49:924-928. Wolfe F, Smythe HA, Yunus MB, Bennett RM et al. The American College Of Rheumatology 1990 criteria for the classification of fibromyalgia; report of the Multicenter Criteria Committe. Arthritis Rheum 1990;33:160-72. Disclosure of Interest: None declared